Autophagy induced by silica nanoparticles protects RAW264.7 macrophages from cell death. (15th March 2017) - Marquardt, Clarissa; Fritsch-Decker, Susanne; Al-Rawi, Marco; Diabaté, Silvia; Weiss, Carsten
Abstract: Although the technological and economic benefits of engineered nanomaterials are obvious, concerns have been raised about adverse effects if such material is inhaled, ingested, applied to the skin or even released into the environment. Here we studied the cytotoxic effects of the most abundant nanomaterial, silica nanoparticles (SiO2 -NPs), in murine RAW264.7 macrophages. SiO2 -NPs dose-dependently induce membrane leakage and cell death without obvious involvement of reactive oxygen species. Interestingly, at low concentrations SiO2 -NPs trigger autophagy, evidenced by morphological and biochemical hallmarks such as autophagolysosomes or increased levels of LC3-II, which serves to protect cells from cytotoxicity. Hence SiO2 -NPs initiate an adaptive stress response which dependent on dose serve to balance survival and death and ultimately dictates the cellular fate.